2015
DOI: 10.1073/pnas.1508224112
|View full text |Cite
|
Sign up to set email alerts
|

Sialyl Lewis x (CD15s) identifies highly differentiated and most suppressive FOXP3 high regulatory T cells in humans

Abstract: SignificanceCD4+ regulatory T (Treg) cells expressing CD25 and the transcription factor forkhead box P3 (FOXP3) play indispensable roles for immunological self-tolerance and homeostasis. Because human FOXP3+CD25+CD4+ T cells are heterogeneous in function and differentiation status, their analysis and manipulation for treating immunological diseases remains a challenge. Here we show that CD15s (sialyl Lewis x) is specifically expressed by activated, terminally differentiated, and most suppressive FOXP3high Treg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
121
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 134 publications
(131 citation statements)
references
References 35 publications
(66 reference statements)
9
121
0
Order By: Relevance
“…In fact, some overlap with known loci for psoriasis and inflammatory bowel disease (7-9), findings consistent with the finding of multiple aberrations in adaptive immunity in patients with sarcoidosis (10)(11)(12). Others have previously demonstrated the significance of reduced levels of nuclear factor-kB (NF-kB)/P65 to sarcoidosis disease severity (12), as well as dysregulation within IL-12 and IL-23 pathways within cutaneous sarcoidosis specimens, using microarray analysis (13).…”
supporting
confidence: 58%
“…In fact, some overlap with known loci for psoriasis and inflammatory bowel disease (7-9), findings consistent with the finding of multiple aberrations in adaptive immunity in patients with sarcoidosis (10)(11)(12). Others have previously demonstrated the significance of reduced levels of nuclear factor-kB (NF-kB)/P65 to sarcoidosis disease severity (12), as well as dysregulation within IL-12 and IL-23 pathways within cutaneous sarcoidosis specimens, using microarray analysis (13).…”
supporting
confidence: 58%
“…6B). In comparison to eTreg cells, cTfr cells had reduced expression of Foxp3, and the previously identified eTreg marker CD15s (35) (Fig. 6C).…”
Section: Il-2 Antagonizes the Formation And Maintenance Of Cd25 − Tfrmentioning
confidence: 63%
“…Thus, there could be positive correlations between Foxp3 + TILs and PD-L1 expression on either IC or TC. A recent study reported that Foxp3 + T reg cells are divided into specific subsets including the highly differentiated and most suppressive Foxp3 + high T reg cells41. We do not know the exact status of T reg cells in previous reports including ours, because previous studies typically used Foxp3 as a representative marker of T reg cells.…”
Section: Discussionmentioning
confidence: 76%